Room temperature phosphorescence of Mn(ii) and Zn(ii) coordination polymers for photoelectron response applications. Issue 29 (27th June 2019) - Yang, Xiao-Gang; Zhai, Zhi-Min; Lu, Xiao-Min; Zhao, Ying; Chang, Xin-Hong; Ma, Lu-Fang
Abstract : Mn(ii ) and Zn(ii ) based coordination polymers have been synthesized, which show different mechanism of room temperature phosphorescence and special photoelectron response performance. Abstract : Room temperature phosphorescence of Mn(ii ) and Zn(ii ) based coordination polymers (Mn-CP and Zn-CP) with a different mechanism was confirmed by experiments and theory calculations. The Mn-CP exhibits high photoelectron response performance while Zn-CP can generate frequency tunable alternating current when the period of on–off illumination is changed.